Analysis of the effects of MIPPO under the anterolateral approach on stress indicators and ankle joint function in patients with open fracture of tibia and fibula - Zhihua Wang; Peipei Xu; Junjun Liao (BMC Surgery)
Abstract Background To compare clinical application value of minimally invasive percutaneous plate osteosynthesis (MIPPO) through anterolateral approach and conventional posterolateral approach, and conduct retrospective analysis of MIPPO surgical methods through different approaches in patients with open tibial and fibular fractures (OTFF), to supply reference for clinical operations. Methods A retrospective analysis was implemented on 84 patients with distal OTFF divided into groups according to different approaches for MIPPO surgery. Patients who received MIPPO treatment through anterolateral approach were in observation group (n = 42), and patients who received MIPPO treatment through conventional posterolateral approach were in the control group (n = 42). The surgical effects, surgical indicators, American Orthopedic Foot and Ankle Society Scoring System (AOFAS) ankle-foot scale scores, stress indicators [substance P (SP), interleukin-6 (IL-6), prostaglandin E2 (PGE2), procalcitonin (PCT) levels, incidence of complications. Results The excellent and good rate of surgery in observation group was 95.24% (40/42); AOFAS score of observation group was higher than that of control group 1 month and 3 months after surgery (P < 0.05); surgical indicators of observation group were better than those of control group (P < 0.05); serum SP, IL-6, PGE2, and PCT levels of observation group were lower than those of control group on 1 and 3 days after surgery (P < 0.05); incidence rate of complications in observation group was 4.76% (2/42). Conclusion Compared with conventional posterolateral approach MIPPO for treatment of patients with distal OTFF, application of anterolateral approach MIPPO has more advantages in optimizing surgical indicators, reducing complications, improving surgical results, and improving ankle joint function, and less stress on body, it has advantages of less trauma and high safety and is worthy of clinical promotion and application.